Health-related quality of life in patients with uveitis. Issue 9 (25th October 2018) - Shamdas, Mohith; Bassilious, Kerolos; Murray, Philip Ian
Abstract : Background/aims: To measure health-related quality of life (HRQOL) in patients with uveitis using time trade-off (TTO) and standard gamble (SG) methods of direct utility analysis. Methods: Consecutive patients attending a tertiary referral uveitis clinic were administered standardised, interview-delivered TTO and SG questionnaires and completed the European Quality of Life Five Dimensions Five Level (EQ5D-5L) questionnaire. Clinical data recorded included best-corrected visual acuity, uveitis anatomical and clinical classifications, duration since diagnosis, disease activity, current medication and any ocular or systemic comorbidities. Results: Two hundred patients with uveitis (124 female, 76 male, median age 54 years) were included. Overall mean TTO utility was 0.831 (95% CI 0.802 to 0.860); mean SG utility was 0.868 (95% CI 0.840 to 0.896) and mean EQ5D-5L utility was 0.742 (95% CI 0.702 to 0.782). There was a negative correlation between visual acuity and mean HRQOL (6/12 or better: TTO 0.86, SG 0.893; 6/15–6/60: TTO 0.662, SG 0.742; worse than 6/60: TTO 0.608, SG 0.712). Poor vision in the better- seeing eye (p=0.004), bilateral disease (p=0.047) and concurrent glaucomatous optic neuropathy (p=0.005) were predictors of poor TTO HRQOL. No correlation was found between HRQOL and duration of diagnosis, a flare of uveitis or being on systemic therapy. Patients with uveitis with poor vision have a TTO value worse than patients with end-stage renal failure on haemodialysis or those with AIDS. Conclusion: Loss of vision resulting from uveitis is associated with reduced HRQOL. The TTO and SG utility values appear directly dependent on the degree of vision loss and not on the duration of disease or systemic medications.